2007
DOI: 10.1099/jmm.0.47155-0
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic valve endocarditis due to Neisseria elongata subsp. elongata in a patient with Klinefelter's syndrome

Abstract: A case is reported of prosthetic valve endocarditis due to Neisseria elongata subsp. elongata in a patient with Klinefelter's syndrome. This is believed to be only the third case of endocarditis reported due to this subspecies. N. elongata is difficult to identify, and is morphologically and biochemically similar to Kingella spp. Sequencing of the 16S rRNA gene is useful for identification. The patient was successfully treated with amoxicillin and gentamicin, followed by ceftriaxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, several Neisseria species other than N. gonorrhoeae and N. meningitidis cause human infections. Neisseria elongata and Neisseria sicca have been isolated from endocarditis (3,5). Neisseria bacilliformis also causes endocarditis and various human infections (4,8,9).…”
mentioning
confidence: 99%
“…However, several Neisseria species other than N. gonorrhoeae and N. meningitidis cause human infections. Neisseria elongata and Neisseria sicca have been isolated from endocarditis (3,5). Neisseria bacilliformis also causes endocarditis and various human infections (4,8,9).…”
mentioning
confidence: 99%
“…In contrast, reports of seven definitive cases, including the present case, excluded the presence of preceding intraoral complications (10)(11)(12)(13)(14)(15). One study evaluating dental risk factors for infective endocarditis demonstrated that only 32.1% of patients infected with dental flora received dental procedures within the previous three months of hospital admission (16), indicating that intraoral organisms often cause endocarditis, regardless of antecedent dental procedures.…”
Section: Discussionmentioning
confidence: 65%
“…However, several Neisseria species other than these two species were also reported as human pathogens [2][3][4][5][6]. In addition to these pathogens, N. skkuensis was designated as a novel species which cause foot ulcer of diabetic patient in 2010 [7].…”
Section: Introductionmentioning
confidence: 99%